IMPROVING THE PHYSICAL HEALTH OF YOUNGER PRESCHOOL CHILDREN - Ashirova, Madina (Журнал иностранных языков и лингвистики, 2021)
The physical health of a person is usually considered as the natural state of the body, which is conditioned by the normal operation of all its systems and organs. Factors such as stress, lack of physical activity, unbalanced diet or bad habits can, as well as other unfavorable conditions, affect not only the social sphere of a person’s life, but can also cause the appearance and development of certain diseases of a chronic nature. In order for the prevention of these diseases to be carried out, a person should lead a healthy lifestyle. It is customary to consider physical development as the basis for a healthy lifestyle